(untitled) (The Pakistan Development Review, 1975)
Research on wage policy issues is a relatively uncommon commodity in Pakistan. The absence of studies of the structure of wages and their trend over time is disturbing in view of the far-reaching effects which the structure of wages has on some of Pakistan’s most pressing development problems—the underutilization of its human resources, the distribution of income and the flow of migrants from rural to urban areas. Policies designed to cope with these problems will in most cases operate through changes in the levels of wages in various branches of the economy. The lack of information on the structure of wages is a rather obvious and substantial barrier to the formulation of appropriate development policies. Reasons for this neglect are not hard to find: reliable and pertinent data are rare, a condition not unrelated to the fact that the structure of wages lends itself to few simple generalizations. In spite of economic theory’s tendency to gloss over the fact, labour is not a homogeneous commodity and wage levels vary among regions, skill groups, and economic sectors as well as within sectors among sub-sectors. Our objective in this study is to explore just one facet of the wage structure in Pakistan : the pattern of inter-industry wage differentials in the large-scale manufacturing sector.